(untitled) (KULT_online, 2018)
In his new monograph, sociologist Asef Bayat ethnographically and historically analyzes the challenges that came with the ‘revolutionary’ phenomenon of the last three decades. Beginning from the Iranian revolution in 1979 till the recent uprisings that hit many Arab countries in 2011, Making Sense of the Arab Spring embraces not only a regional but also a global comparative approach. The book illustrates what a radical change means (or does not mean) for the people, who initiate such uprising in confrontation with the respective regimes and authorities in charge. Although Bayat traces the unfortunate absence of any sign of revolutionaries and revolutionary ideas shortly after their emergence in the streets, he closes on a hopeful note, inviting the readers to think about new horizons that can lead to “imagining and working for alternative futures” (p. 223).